Collectively Enhanced Giant Circular Dichroism of Germanium Nanohelix Square Lattice Arrays - Ellrott, Günter; Beck, Paul; Sultanov, Vitaliy; Rothau, Sergej; Lindlein, Norbert; Chekhova, Maria; Krstic, Vojislav (Advanced Photonics Research, 2023)
Circular dichroism is a unique chiroptical signature of the chirality of a system and is a prevalent way to characterize and distinguish systems on a fundamental level and for their technological applicability. Thus, engineering and maximizing the chiroptical response of a single chiral object or a metasurface composed of chiral entities is a formidable task. Current efforts strongly focus on individual metallic nanostructures and their periodic ensembles to harvest on (resonant) plasmonic properties and interactions. This route, however, waives the advantages of high-refractive-index nanoscale materials embracing low dissipative losses at optical wavelengths and electromagnetic fields penetrating and propagating in such materials. Herein, a strong circular dichroism is demonstrated in square lattices of nanohelices made of the high-refractive-index semiconductor germanium, with dissymmetry factors outperforming metal-based ensembles. The observation of a much higher dissymmetry emerges for illumination with spatially coherent light, in comparison to spatially incoherent light. High dissymmetry is attributed to cooperative coupling between single helices, resulting from the combination of dielectric resonances of both the individual helical building blocks and the highly ordered lattice.<br

Entangled photons from subwavelength nonlinear films - Santiago-Cruz, Tomas; Sultanov, Vitaliy; Zhang, Haizhong; Krivitsky, Leonid A.; Chekhova, Maria (Optics Letters, 2021)
Miniaturized entangled photon sources, in particular based on subwavelength metasurfaces, are highly demanded for the development of integrated quantum photonics. Here, as a first step towards the development of quantum optical metasurfaces (QOMs), we demonstrate generation of entangled photons via spontaneous parametric down-conversion (SPDC) from subwavelength films. We achieve photon pair generation with a high coincidence-to-accidental ratio in lithium niobate and gallium phosphide nanofilms. By implementing the fiber spectroscopy of SPDC in nanofilms, we measure a spectrum with a bandwidth of 500 nm, limited only by the overall detection efficiency. The spectrum reveals vacuum field enhancement due to a Fabry-Perot resonance inside the nonlinear films. It also suggests a strategy for observing SPDC from QOM. Our experiments lay the groundwork for future development of flat SPDC sources, including QOM. (C) 2021 Optical Society of America
CRIS-Team WoS Importer:2021-03-19

Flat-optics generation of broadband photon pairs with tunable polarization entanglement - Sultanov, Vitaliy; Santiago Cruz, Tomás; Chekhova, Maria (Optics Letters, 2022)
The concept of “flat optics” is quickly conquering different fields of photonics, but its implementation in quantum optics is still in its infancy. In particular, polarization entanglement, strongly required in quantum photonics, is so far not realized on “flat” platforms. Meanwhile, relaxed phase matching of “flat” nonlinear optical sources enables enormous freedom in tailoring their polarization properties. Here we use this freedom to generate photon pairs with tunable polarization entanglement via spontaneous parametric downconversion (SPDC) in a 400-nm GaP film. By changing the pump polarization, we tune the polarization state of photon pairs from maximally entangled to almost disentangled, which is impossible in a single bulk SPDC source. Polarization entanglement, together with the broadband frequency spectrum, results in an ultranarrow (12 fs) Hong–Ou–Mandel effect and promises extensions to hyperentanglement.
CRIS-Team Scopus Importer:2022-08-12

Liquid crystals as new tunable sources of entangled photon pairs - Kavčič, Aljaž; Sultanov, Vitaliy; Kokkinakis, Emmanouil; Sebastián, Nerea; Chekhova, Maria; Humar, Matjaž (Photonics for Quantum 2024, 2024)
Entangled photon pair sources relying on spontaneous parametric down-conversion (SPDC) are an essential ingredient for optical quantum technologies.1 Currently, the vast majority of SPDC sources is based on solid-state crystals. However, their rigid nature implies a careful design of the source as well as it limits the two-photon state that can be generated, without much possibility of tuning it. Here, we demonstrate a new generation of efficient, highly tunable sources of entangled photons based on recently discovered liquid crystal materials called ferroelectric nematic liquid crystals (FNLC).2,3 In addition to other highly desirable properties that liquid crystals possess, such as the ability to self-assemble into complex structures, strong response to the electric field and integrability into complex optical systems,4 FNLCs also possess considerable optical nonlinearity.5,6 This, as we demonstrate, enables also efficient SPDC generation and opens the door for promising new functionalities in quantum technologies. This work demonstrates the first-ever realization of SPDC in soft, organic matter, with the possibility of controlling the molecular order and thus tuning the two-photon polarization state. We show that almost any polarization state can be generated by simply adjusting the twist of the molecular orientation along the sample. Additionally, by applying only a few volts, we can drastically alter both the emission rate and the generated state of photon pairs, which enables real-time tunability. Developed concepts could lead to complex multi-pixel devices generating quantum light with real time tunability and therefore hold the potential to have a huge impact in the field of quantum technologies.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Entanglement; Liquid crystals; Photon pairs; Spontaneous parametric down-conversion; Tunable source

Photon pairs bi-directionally emitted from a resonant metasurface - Son, Changjin; Sultanov, Vitaliy; Santiago Cruz, Tomás; Anthur, Aravind P. P.; Zhang, Haizhong; Paniagua-Dominguez, Ramon; Krivitsky, Leonid; Kuznetsov, Arseniy I. I.; Chekhova, Maria (Nanoscale, 2023)
Metasurfaces are artificially structured surfaces able to control the properties of light at subwavelength scales. While, initially, they have been proposed as means to control classical optical fields, they are now emerging as nanoscale sources of quantum light, in particular of entangled photons with versatile properties. Geometric resonances in metasurfaces have been recently used to engineer the frequency spectrum of entangled photons, but the emission directivity was so far less studied. Here, we generate photon pairs via spontaneous parametric down conversion from a metasurface supporting a quasi-bound state in the continuum (BIC) leading to remarkable emission directivities. The pair generation rate is enhanced 67 times compared to the case of an unpatterned film of the same thickness and material. At the wavelength of the quasi-BIC resonance, photons are mostly emitted backwards, while their partners, spectrally detuned by only 8 nm, are emitted forwards. This behavior demonstrates fine spectral splitting of entangled photons and their bi-directional emission, never before observed in nanoscale sources. We expect this work to be a starting point for the efficient demultiplexing of photons in nanoscale quantum optics.
CRIS-Team WoS Importer:2023-02-10

Photon Pairs from Resonant Metasurfaces - Santiago-Cruz, Tomás; Fedotova, Anna; Sultanov, Vitaliy; Weissflog, Maximilian A.; Arslan, Dennis; Younesi, Mohammadreza; Pertsch, Thomas; Staude, Isabelle; Setzpfandt, Frank; Chekhova, Maria (Nano Letters, 2021)
All-dielectric optical metasurfaces are a workhorse in nano-optics, because of both their ability to manipulate light in different degrees of freedom and their excellent performance at light frequency conversion. Here, we demonstrate first-time generation of photon pairs via spontaneous parametric-down conversion in lithium niobate quantum optical metasurfaces with electric and magnetic Mie-like resonances at various wavelengths. By engineering the quantum optical metasurface, we tailor the photon-pair spectrum in a controlled way. Within a narrow bandwidth around the resonance, the rate of pair production is enhanced up to 2 orders of magnitude, compared to an unpatterned film of the same thickness and material. These results enable flat-optics sources of entangled photons - a new promising platform for quantum optics experiments.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Mie-type resonances; nonlinear metasurfaces; photon-pair generation; quantum optics; spontaneous parametric down-conversion

Spontaneous Parametric Down-Conversion in Nonlinear Metasurfaces - Fedotova, Anna; Santiago Cruz, Tomás; Sultanov, Vitaliy; Weissflog, Maximilian; Younesi, Mohammadreza; Staude, Isabelle; Pertsch, Thomas; Setzpfandt, Frank; Chekhova, Maria (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Resonant nonlinear metasurfaces gained a lot of interest in the past decade because of their unique features such as subwavelength thickness and ability to control spatial and temporal properties of light. They have proved to be efficient for classical processes such as second-harmonic generation (SHG), but their potential in quantum nanophotonics - for example for biphoton generation via spontaneous parametric down-conversion (SPDC) - remained mostly unexplored. Recently, SPDC at the nanoscale was established in nonlinear thin films [1] and implied in single nanoresonators [2], albeit with very low efficiency.
CRIS-Team Scopus Importer:2021-10-29

Temporally Distilled High-Dimensional Biphotonic States from Thin Sources - Sultanov, Vitaliy; Chekhova, Maria (ACS Photonics, 2024)
Generation of entangled photons through spontaneous parametric down-conversion (SPDC) from micro- and nanoscale sources offers unprecedented freedom in quantum state engineering, including the ability to generate two-photon states with high-dimensional hyperentanglement. However, as the source of SPDC gets smaller, the role of photoluminescence increases, which leads to the contamination of two-photon states with a thermal background. Here we propose and implement a solution to this problem: by using pulsed SPDC and time distillation, we increase the purity and the heralding efficiency of the photon pairs. In the experiment, we increased the purity of the two-photon states generated in a 7 μm film of lithium niobate from 0.002 to 0.99. With the higher purity we were able to observe and characterize different polarization states of photon pairs generated simultaneously due to relaxed phase matching. In particular, we showed the presence of orthogonally polarized photons that are potentially usable for the generation of polarization entanglement.
CRIS-Team Scopus Importer:2024-02-09
Keywords: distillation; nanoscale; photon pairs; purity

Tunable entangled photon-pair generation in a liquid crystal - Sultanov, Vitaliy; Kavčič, Aljaž; Kokkinakis, Emmanouil; Sebastián, Nerea; Chekhova, Maria; Humar, Matjaž (Nature, 2024)
Liquid crystals, with their ability to self-assemble, strong response to an electric field and integrability into complex systems, are key materials in light-beam manipulation1. The recently discovered ferroelectric nematic liquid crystals2,3 also have considerable second-order optical nonlinearity, making them a potential material for nonlinear optics4,5. Their use as sources of quantum light could considerably extend the boundaries of photonic quantum technologies6. However, spontaneous parametric down-conversion, the basic source of entangled photons7, heralded single photons8 and squeezed light9, has so far not been observed in liquid crystals—or in any liquids or organic materials. Here we implement spontaneous parametric down-conversion in a ferroelectric nematic liquid crystal and demonstrate electric-field tunable broadband generation of entangled photons, with an efficiency comparable to that of the best nonlinear crystals. The emission rate and polarization state of photon pairs is markedly varied by applying a few volts or twisting the molecular orientation along the sample. A liquid-crystal source enables a special type of quasi-phase matching10, which is based on the molecular twist structure and is therefore reconfigurable for the desired spectral and polarization properties of photon pairs. Such sources promise to outperform standard nonlinear optical materials in terms of functionality, brightness and the tunability of the generated quantum state. The concepts developed here can be extended to complex topological structures, macroscopic devices and multi-pixel tunable quantum light sources.
CRIS-Team Scopus Importer:2024-06-21

Tunable liquid-crystal source of photon pairs - Sultanov, Vitaliy; Kavčič, Aljaž; Kokkinakis, Manolis; Humar, Matjaž; Chekhova, Maria (CLEO: Science and Innovations 2024, 2024)
We demonstrate a liquid-crystal broadband source of entangled photons, whose flux and polarization are tunable through the electric field or molecular twist. This opens a path to a new generation of tunable quantum light sources.
CRIS-Team Scopus Importer:2024-10-04